Radiolabeled Complex of Antimicrobial Peptides UBI29-41 and UBI18-35 Labeled with 99mTc for Differential Diagnosis of Bone Infection of the Limbs; Bulletin of Experimental Biology and Medicine; Vol. 170, iss. 4 - Zavadovskaya V. D. Vera Dmitrievna; Larkina M. S. Mariya Sergeevna; Stasyuk (Stasiuk) E. S. Elena Sergeyevna; Zorkaltsev M. A. Maksim Aleksandrovich; Udodov V. D. Vladimir Dmitrievich; Ivanov V. V. Vladimir Vladimirovich; Shevtsova N. M. Nataljya Mikhaylovna; Rogov A. S. Alexander Sergeyevich; Lushchik A. Ya. Aleksandr Yakovlevich; Yantsevich A. V. Aleksey Viktorovich; Belousov M. V. Mikhail Valerievich; Baykov A. N. Aleksandr Nikolaevich; et al. (2021, 2021)
Title screen